Foreign Body in Root Canals of Two Adjacent Deciduous Molars: A Case Report - Singh Dhull, Kanika (Jaypee Brothers Medical Publishers, 2013)
Children often tend to have the habit of inserting foreign objects in the oral cavity unknowingly for relief of dental pain. Sometimes, children do not reveal to their parents due to fear. These foreign objects may act as a potent source of infection and painful condition. The discovery of foreign bodies in the teeth is a special situation, which is often diagnosed accidentally. Detailed case history, clinical and radiographic examinations are necessary to come to a conclusion about the nature, size, location of the foreign body and the difficulty involved in its retrieval. Here is a case report, where foreign object was accidentally lodged in the carious deciduous molars by a child. How to cite this article: Dhull KS, Acharya S, Ray P, Dhull RS. Foreign Body in Root Canals of Two Adjacent Deciduous Molars: A Case Report. Int J Clin Pediatr Dent 2013;6(1):38-39.